2021
DOI: 10.1001/jama.2021.7939
|View full text |Cite
|
Sign up to set email alerts
|

Acute Treatments for Episodic Migraine in Adults

Abstract: IMPORTANCEMigraine is common and can be associated with significant morbidity, and several treatment options exist for acute therapy.OBJECTIVE To evaluate the benefits and harms associated with acute treatments for episodic migraine in adults.DATA SOURCES Multiple databases from database inception to February 24, 2021.STUDY SELECTION Randomized clinical trials and systematic reviews that assessed effectiveness or harms of acute therapy for migraine attacks.DATA EXTRACTION AND SYNTHESIS Independent reviewers se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 145 publications
(154 reference statements)
1
81
0
Order By: Relevance
“…Recently, Abdel Shaheed analyzed data from 36 publications and reported that paracetamol produced modest pain relief in hip and knee osteoarthritis, tension headache, and post-craniotomy pain and that it was ineffective in other conditions [ 145 ]; the authors concluded with the need for large, high-quality trials to reduce uncertainty about the efficacy of paracetamol in common pain conditions. In the last few months, new published studies report the safe use of paracetamol in patients with chronic kidney disease [ 147 ], the significant efficacy of paracetamol for post-arthroplasty pain [ 148 ], the lesser efficacy of paracetamol than ibuprofen for post-laminectomy pain [ 149 ], the opioid-sparing effects of paracetamol in the Emergency Department [ 150 ], the recommendations against paracetamol in lumbar spinal stenosis with neurogenic claudication [ 151 ], and the recommendations in favor of paracetamol for postcesarean pain [ 152 ] and for migraine [ 153 , 154 ].…”
Section: Recent Findings and Future Directionsmentioning
confidence: 99%
“…Recently, Abdel Shaheed analyzed data from 36 publications and reported that paracetamol produced modest pain relief in hip and knee osteoarthritis, tension headache, and post-craniotomy pain and that it was ineffective in other conditions [ 145 ]; the authors concluded with the need for large, high-quality trials to reduce uncertainty about the efficacy of paracetamol in common pain conditions. In the last few months, new published studies report the safe use of paracetamol in patients with chronic kidney disease [ 147 ], the significant efficacy of paracetamol for post-arthroplasty pain [ 148 ], the lesser efficacy of paracetamol than ibuprofen for post-laminectomy pain [ 149 ], the opioid-sparing effects of paracetamol in the Emergency Department [ 150 ], the recommendations against paracetamol in lumbar spinal stenosis with neurogenic claudication [ 151 ], and the recommendations in favor of paracetamol for postcesarean pain [ 152 ] and for migraine [ 153 , 154 ].…”
Section: Recent Findings and Future Directionsmentioning
confidence: 99%
“…Triptans, nonsteroidal anti-inflammatory drugs (NSAIDs), topiramate, and the newer monoclonal antibodies (mAbs) were prescribed to these patients based on local availability and best practices, frequency of attacks, the physicians' therapeutic knowledge of the risk profile of the selected medicine, and other comorbidities such as BMI and smoking status. Several factors determine the precise pharmacological choice in each situation [1,2,[4][5][6][9][10][11][12][13][14][15][16][17][20][21][22][23][24], including the nature and severity of the migraine, the presence and severity of comorbidities, the most expedient route of administration at presentation (transdermal, intranasal, intravenous, intramuscular, or oral), safety and side effect profile, and, most importantly, the patient's treatment response. Furthermore, some writers and recommendations have advocated a stratified and personalized therapy strategy [1,2,[4][5][6][9][10][11][12][13][14][15][16][17][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors determine the precise pharmacological choice in each situation [1,2,[4][5][6][9][10][11][12][13][14][15][16][17][20][21][22][23][24], including the nature and severity of the migraine, the presence and severity of comorbidities, the most expedient route of administration at presentation (transdermal, intranasal, intravenous, intramuscular, or oral), safety and side effect profile, and, most importantly, the patient's treatment response. Furthermore, some writers and recommendations have advocated a stratified and personalized therapy strategy [1,2,[4][5][6][9][10][11][12][13][14][15][16][17][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic options described above demonstrate, with a large degree of strength, the evidence of the efficacy (limited only for opioids [ 40 ]) and the great translational success of the research effort of the last 30 years; however, a safe abortive treatment for acute attacks effective in most patients is still lacking. Recently, potassium channels have gained interest in the field of migraine.…”
Section: Novel Perspectives and Future Directions: Focus On Eptinezumabmentioning
confidence: 99%